Propuesta de creación del departamento de comunicación para Amatic - Salazar Zotaminga, Evelyn Paulina (2015)
This project is a proposal to create the communication department AMATIC, an organization dedicated to providing education on issues related to electronic, electrical and systems. To do this as a starting point an investigation with theory on organizational communication and processes that develop internal and external organizations was performed. After a communicative situation assessment to identify and describe the current situation of AMATIC was elaborated, learn about opportunities for improvement and building needs; thus developing appropriate for organizational growth strategies. Finally, a proposal for the creation of the department aimed at organizing the interaction processes AMATIC staff communication was done through lines of action and activities that help improve the productivity and competitiveness of the organization.